CT measurements of the proximal femoral medullary cavity in healthy adults: a cross-sectional study - Ran Zhao,; Cai, Hong; Tian, Hua; Zhang, Ke (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the proximal femoral morphology on three-dimensional reconstructed imagery to explore the factors influencing the relevant parameters. Method: The cross-sectional study was conducted at Peking University Third Hospital in northern China from January 2019 to August 2020, and comprised healthy adults who underwent computed tomography scanning. Three-dimensional computed tomography reconstruction of the proximal femoral medullary cavity was performed using Mimics 22. The anatomical parameters related to total hip arthroplasty were measured to examine the relationship among gender, age and femoral length. Data was analysed using SPSS 20. Results: Of the 63 adults, meaning 126 hips, 21(33.3%) were males, meaning 42(33.3%) hips, and 42(66.6%) were females, meaning 84(66.6%) hips. The overall mean age was 51.5±23.1 years (range: 23-68 years). The inflection point of the medullary cavity curved at 5-10mm distal to the lesser trochanteric line. Most horizontal plane parameters significantly differed between men and women (p<0.05), with the mean medullary cavity being wider in men than women. There was a significant difference between the genders in the sagittal anterior-posterior diameter of the canal flare index (p<0.05). Age was negatively correlated with the coronal medial-lateral diameter and coronal lateral diameter of canal flare index. In the coronal and sagittal planes, there was a positive correlation between the metaphysis and diaphysis, and the coronal and sagittal planes were positively correlated with the orthogonal plane. Conclusions: Femoral morphology could be influenced by gender and age. Morphological changes of the proximal femoral medullary cavity were not present in a single plane, but were affected by multiple planes. When the diameter of one plane became larger, its orthogonal plane concomitantly increased. Key Words: Proximal femoral, Morphology, CT measurement, Correlation.